Heart rhythm assessment in elite endurance athletes: A new method? - Ausland, Â.; Sandberg, E. L.; Jostveit, J.; Seiler, S. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Cardiac arrhythmias (CA), especially atrial fibrillation (AF), are relatively common among elite endurance athletes. Conventional diagnostic tools for assessment of rhythm disorders suffer from limited availability, limited test duration time, and usability challenges, particularly during the demanding conditions of an elite athlete training many hours each day. In endurance athletes, there is a need for out-of-hospital monitoring and detection of arrhythmias under conditions that are relevant and potentially provocative. The Norwegian patch ECG247 Smart Heart Sensor has been developed to simplify the assessment of heart rhythm disorders. The current study aimed to evaluate the ECG247 Smart Heart Sensor function and practicalities in an elite athlete environment.